Analisis Pembelajaran PAI dan Budi Pekerti Materi SKI di SMAN 1 Pariangan dan SMAN 2 Batusangkar - Wijaya, Putu Albiansyah; Arben, Arben; Fadriati, Fadriati (YASIN, 2024)
The Element of Sejarah Kebudayaan Islam (SKI) is one of the important elements in the PAI and Budi Pekerti learning materials at the high school level. However, SKI materials are often considered boring and less popular. To overcome this, it is necessary to analyze how the learning process is carried out. The purpose of this study was to analyze and describe the PAI and Budi Pekerti learning process for SKI materials at the planning, implementation, and evaluation stages. The study was conducted qualitatively using the field research method by collecting data in the field through interviews with PAI teachers and documentation studies on the PAI and Budi Pekerti Teaching Module for SKI materials. The results of the data collection were processed and analyzed by considering the context and interests of the study. The results of the study showed that at the planning stage, teaching modules, media used, and other supporting facilities and tools were prepared. The implementation was carried out in accordance with the design in the Teaching Module and modified according to conditions and needs during the learning process. Evaluation was carried out in formative form to evaluate the learning process and summative to evaluate learning outcomes.